Rebellion Against Family In Haruki Murakami's After Dark (2004) : A Psychoanalytic Approach - Rahmawati, Mega, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
This research paper aims to know the rebellion against family of the major characters reflected in Haruki Murakami's After Dark novel. The objective of the research is to analyze the novel based on the structural elements and to reveal the rebel against family of the major characters by means in the Haruki Murakami's After Dark novel (2004) by using Psychoanalytic approach. The type of this research is descriptive qualitative. The data of the research is the primary data of the research is The After Dark novel by Haruki Murakami. The secondary data of the research taken from any information related to the novel such as books, other source and website that related to the study. The technique of collecting data are reading novel, arranging the data into several part based on its classification, selecting the data by rejecting the irrelevant information which does not support the topic of the study, and drawing the conclusion. The method to analyze of this data is descriptive analysis. Based on structural elements of the novel, the writer delivers a moral message that "children rebellion in the family is one of the symbols of relationship dissatisfaction". Based on the psychoanalytic approach, the author illustrates psychoanalytic phenomenon which Mari's rebellion appears because her nature formed from the uncomfortable feeling at home. Based on her Id where she really needs care and love from her parent and her sister but she can not get it. This kind of id finally forms her ego, where she makes decision to go out and leave the house without care about her family feelings.